Histopathological pattern of malignancy in solitary thyroid nodule (Bangladesh Journal of Otorhinolaryngology, 2012)
Objective: To find out relative frequency and type of malignancy in solitary thyroid nodule (STN).Methods: This cross sectional study done in the Department of Otolaryngology Head & Neck Surgery, Dhaka Medical College Hospital (DMCH), Dhaka and Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka during the period of July 2008 to June 2009. For this study, 118 patients who were admitted a case of solitary thyroid nodule for operation. Diagnosed the case by detailed history, clinical examination, investigations, analyzed data presented by various tables, graphs and figures. Total 118 patients were selected as per described criteria from the Department of otolaryngology and head-neck surgery DMCH & BSMMU, Dhaka from July 2008 to July 2009.Results: In this study of 118 patients of STN, majority of the patients were within 21-40 years age group with female predominance. In thyroid malignancy male and female ratio was 1:1.75. Among 118 cases of solitary thyroid nodule 22 cases were malignant. Out of 22 malignant cases, 16(73%) were papillary carcinoma, 4(18%) were follicular carcinoma and 2(9%) were anaplastic carcinoma. Thyroid swelling was the common presentation in all cases (100%), some patients also presented with other symptoms like cervical lymphadenopathy in 6 (5.08%) cases, dysphagia 2(1.69%) cases and hoarseness of voice 1(0.85%) case. Study showed very significant difference (p